Potential Pathway of Nitrous Oxide Formation in Plants - Timilsina, Arbindra; Zhang, Chuang; Pandey, Bikram; Bizimana, Fiston; Dong, Wenxu; Hu, Chunsheng (Frontiers in Plant Science, 2020)
Plants can produce and emit nitrous oxide (N2O), a potent greenhouse gas, into the atmosphere, and several field-based studies have concluded that this gas is emitted at substantial amounts. However, the exact mechanisms of N2O production in plant cells are unknown. Several studies have hypothesised that plants might act as a medium to transport N2O produced by soil-inhabiting microorganisms. Contrarily, aseptically grown plants and axenic algal cells supplied with nitrate (NO3) are reported to emit N2O, indicating that it is produced inside plant cells by some unknown physiological phenomena. In this study, the possible sites, mechanisms, and enzymes involved in N2O production in plant cells are discussed. Based on the experimental evidence from various studies, we determined that N2O can be produced from nitric oxide (NO) in the mitochondria of plants. NO, a signaling molecule, is produced through oxidative and reductive pathways in eukaryotic cells. During hypoxia and anoxia, NO3 in the cytosol is metabolised to produce nitrite (NO2), which is reduced to form NO via the reductive pathway in the mitochondria. Under low oxygen condition, NO formed in the mitochondria is further reduced to N2O by the reduced form of cytochrome c oxidase (CcO). This pathway is active only when cells experience hypoxia or anoxia, and it may be involved in N2O formation in plants and soil-dwelling animals, as reported previously by several studies. NO can be toxic at a high concentration. Therefore, the reduction of NO to N2O in the mitochondria might protect the integrity of the mitochondria, and thus, protect the cell from the toxicity of NO accumulation under hypoxia and anoxia. As NO3 is a major source of nitrogen for plants and all plants may experience hypoxic and anoxic conditions owing to soil environmental factors, a significant global biogenic source of N2O may be its formation in plants via the proposed pathway.